Efficacy and safety of insulin glargine 300 units/mL vs insulin degludec in patients with type 1 and type 2 diabetes: a systematic review and meta-analysis - Alhmoud, Eman N.; Saad, Mohamed Omar; Omar, Nabil Elhadi (Frontiers in Endocrinology, 2024)
Background Ultra-long-acting insulin analogs [insulin degludec (IDeg) and insulin glargine 300 units/mL (IGla-300)] offer a longer duration of action with less risk of hypoglycemia compared to other long-acting insulins. However, data about the comparative efficacy and safety are inconsistent. Methods We searched CENTRAL, PubMed, Embase, ICTRP Search Portal, and ClinicalTrials.gov on 7 October 2022. Randomized controlled trials (RCTs) comparing the safety and efficacy of IDeg (100 or 200 units/mL) and IGla-300 in patients with type 1 or type 2 diabetes were included. Three review authors independently selected trials, assessed the risk of bias, extracted data, and evaluated the overall certainty of the evidence using GRADE. The primary outcomes were the change in glycated hemoglobin (HbA1c) and any hypoglycemia; the secondary outcomes were the change in fasting plasma glucose (FPG) and severe and nocturnal hypoglycemia. Results Four open-label RCTs were included (2727 participants), 3 parallel and 1 cross-over. Overall, the risk of bias assessment yielded some concern or high risk. There was a comparable change in HbA1c from baseline to the end of treatment, a mean difference of 0.07% (95% confidence interval (CI) 0.06 – 0.19; p = 0.29; 3 trials; 2652 patients; very low-certainty evidence), and a comparable rate of any hypoglycemia, rate ratio 1.02 (95% CI 0.8 – 1.3; p = 0.87; 3 trials; 2881 patients; very low-certainty evidence). IDeg resulted in more reduction in FPG compared to IGla-300, mean difference of 10.27 mg/dL (95% CI 7.25 – 13.29; p < 0.001; 3 trials; 2668 patients; low-certainty evidence). Similar rates of nocturnal and severe hypoglycemia were observed, rate ratio of 1.13 (95% CI 0.72 – 1.78; p = 0.54; 3 trials; 2668 patients; very low-certainty evidence) and 1.4 (95% CI 0.41 – 4.73; p = 0.59; 2 trials; 1952 patients; very low-certainty evidence), respectively. Conclusion There is no evidence of a difference between IDeg and IGla-300 in the mean change in HbA1c and the risk of anytime, nocturnal, and severe hypoglycemia. IDeg appeared to cause a higher reduction in FPG compared to IGla-300. However, this finding should be interpreted with caution due to the small number of trials included and their high risk of bias. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022364891, identifier CRD42022364891.